Utilizing Social Media and Creating Creative Content as a Means of Digital Tourism Branding: Pengabdian - Joice Soraya; Riris Lawitta; Audisty Prana Hardayu; Sriwanti Belani; Nindy Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The community-based tourism sector in various regions of the Indonesian archipelago, such as Java, Sumatra, Kalimantan, and Sulawesi, holds enormous potential, but is often hampered by limited marketing reach and suboptimal use of digital technology. This community service (PkM) activity aims to increase the capacity of tourism destination managers to utilize social media and produce creative content as an effective tourism branding tool in these four strategic regions. The activity was implemented through technical guidance (bimtek) methods, including digital literacy training, visual and audiovisual content creation workshops, and direct assistance with strategies for optimizing Instagram and TikTok platforms. The target audience for this activity was tourism awareness groups (Pokdarwis) and micro-businesses around local tourist destinations. The activity results showed a significant increase in partners' understanding of social media aesthetics (feeds and reels), attractive photography techniques, and content calendar development. Furthermore, this activity succeeded in producing a number of creativecontent that was immediately uploaded, resulting in increased audience interaction (engagement rates) on tourism social media in each region.